Behavioral Finance in The Field of Compensation - Dovlatyan, Hasmik; Asryan, Lilit; Sahakyan, Gnel (Bulletin of Yerevan University G: Economics, 2025)
Behavioral finance in the field of compensation studies how psychological, social, and cognitive factors influence decision-making in aspects such as salary payment, compensation, and other elements of employment relationships․ This field combines economic theory with psychological and sociological concepts to understand how people perceive and respond to different payment and reward systems․ Within the scope of this article, a survey was conducted among 100 employed individuals over the age of 18, the analysis of which will highlight the key differences between traditional economics and behavioral economics more clearly.
Keywords: behavioral finance; remuneration; salary; motivation; job satisfaction; pay fairness; framing effect